Optimalisasi Pertumbuhan Bunga Kamboja melalui Penyuluhan dan Pemberian Pupuk Cair Ampas Tebu pada Kelompok Ibu-Ibu PKK RT 23 di Kelurahan Pasir Putih, Kota Jambi - Nasution, Hasriati; Saad, Asmadi; Yusfaneti (WIDA Publishing, 2023)
Frangipani flowers, renowned for their beauty and fragrance, are commonly found in various places in Indonesia, ranging from gardens, home yards, office gardens, to street gardens. However, frangipani tree trunks produce a white latex that can cause skin irritation. To enhance the growth and beauty of frangipani flowers, it is essential to fulfill the plant's nutrient requirements, and one solution is to use sugarcane bagasse as organic fertilizer. Sugarcane bagasse is rich in carbohydrates, carbon, protein, calcium, phosphorus, iron, and sodium. Additionally, sugarcane bagasse contains lignocellulose, beneficial as a biomass material. The use of liquid organic fertilizer from sugarcane bagasse can stimulate plant growth, especially during the vegetative to generative phases. This research aims to improve the skills of the PKK women in RT 23, Pasir Putih Subdistrict, Jambi City, in cultivating frangipani flowers by providing guidance on the production and use of liquid organic fertilizer from sugarcane bagasse. The guidance is conducted in two stages, providing materials on making liquid organic fertilizer from coconut coir and demonstrating its application in growing frangipani flowers using pots. The community service team provides flower cuttings, polybags, sugarcane bagasse, equipment, covered buckets, soil media, and water for the smooth implementation. The results of the guidance show high enthusiasm among the PKK women in RT 23, Pasir Putih. With this increased knowledge, it is expected that they can produce liquid organic fertilizer from sugarcane bagasse in appropriate doses to support the growth and beauty of frangipani flowers.